2016
DOI: 10.1111/fcp.12216
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of PF‐4708671 against N‐methyl‐d‐aspartic acid‐induced retinal damage in rats

Abstract: We previously demonstrated that rapamycin, an inhibitor of the mammalian target of rapamycin (mTOR), protects against N-methyl-d-aspartic acid (NMDA)-induced retinal damage in rats. Rapamycin inhibits mTOR activity, thereby preventing the phosphorylation of ribosomal protein S6, which is a downstream target of S6 kinase. Therefore, we aimed to determine whether PF-4708671, an inhibitor of S6 kinase, protects against NMDA-induced retinal injury. Intravitreal injection of NMDA (200 nmol/eye) caused cell loss in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Inhibition of specific downstream targets of mTOR signaling may offer a more selective approach, potentially making it more beneficial for ASD therapy. We used PF-4708671, which is a highly specific inhibitor of S6K1 and of benefit in several neurological disorders, to conduct the current study (Hayashi et al, 2016 ; Pearce et al, 2010 ; Srivastava et al, 2016 ). The decreased cerebral blood flow resulting from the blockade of the S6K1 branch of mTOR signaling could potentially offer therapeutic benefits in the treatment of tuberous sclerosis-ASD in humans (Gkogkas et al, 2013 ; Kelleher & Bear, 2008 ; Sharma & Mehan, 2021 ; Winden et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of specific downstream targets of mTOR signaling may offer a more selective approach, potentially making it more beneficial for ASD therapy. We used PF-4708671, which is a highly specific inhibitor of S6K1 and of benefit in several neurological disorders, to conduct the current study (Hayashi et al, 2016 ; Pearce et al, 2010 ; Srivastava et al, 2016 ). The decreased cerebral blood flow resulting from the blockade of the S6K1 branch of mTOR signaling could potentially offer therapeutic benefits in the treatment of tuberous sclerosis-ASD in humans (Gkogkas et al, 2013 ; Kelleher & Bear, 2008 ; Sharma & Mehan, 2021 ; Winden et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that leukocyte infiltration and microglial activation in the retina occurred one day after intravitreal injection of NMDA in rats [ 26 , 38 , 39 , 40 ]. Infiltrating leukocytes and activated microglia promote retinal inflammation and exacerbate neuronal damage [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Histological evaluation was performed according to the methods described in our previous studies [ 25 , 26 , 37 , 38 , 40 ]. Briefly, seven days after injection, rats were deeply anesthetized with pentobarbital sodium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation